Efficacy, safety, and predictability of transepithelial photorefractive keratectomy: meta-analysis. Issue 5 (May 2021) - Sabau, Alexandra; Daas, Loay; Behkit, Abdelshafi; Wagenpfeil, Stefan; Langenbucher, Achim; Ardjomand, Navid; Flockerzi, Elias; Seitz, Berthold
Abstract : This meta-analysis suggested that TransPRK performed by the Schwind Amaris laser had high safety, efficacy, and predictability in the correction of myopia and/or astigmatism. Abstract : Purpose: To evaluate the efficacy, safety, and predictability of transepithelial photorefractive keratectomy (TransPRK) for correcting myopia, astigmatism, and hyperopia. Setting: Department of Ophthalmology, Saarland University Medical Center, Homburg/Saar, Germany. Design: Meta-analysis of retrospective or prospective studies. Methods: Relevant studies were collected from Medline and included when meeting the following predefined criteria: randomized controlled trials, at least 1 of the main outcome measures as efficacy, safety, or predictability, and 1 common TransPRK laser (Schwind Amaris). The parameters estimates and 95% CI were derived from random-effects meta-analysis to account for possible heterogeneity. Results: Because hyperopia studies did not meet the inclusion criteria, the results are centered on myopia and astigmatism. Sixteen studies with a total of 1924 treated eyes were included in the meta-analysis. The mean efficacy, safety, and predictability had a probability of 94% (CI, 0.86-0.97), 0% (CI, 0.00-0.03), and 89% (CI, 0.82-0.93), respectively. The mean correction index, difference vector, and index of success had a value of 1.01 (CI, 1.01-1.02), 0.20 (CI, 0.06-0.34), and 0.12 (CI, 0.07-0.18), respectively. Conclusions: This summary estimate showed that TransPRK was highly effective, safe, and predictable in correcting myopia and/or astigmatism.